The combined workout in juvenile basketball example of physical and technique special training - Izzo, R.; Biancalana, V. (Science, Movement & Health, 2014)
The following paper talks about sport practice nowadays in a new view, no more dividing athletic workout and sport specific technical one. The problem is not so easy to solve, and many sport operators are working with them own solving philosophy. What we are going to propose is introducing is a very experienced methodology. Our idea is a reasonable mix between athletic and technical workout, sure that is nothing genial to finally resolve the problem. The aim. of the research-So that what we are going to introduce is a plan of combined workout, specific for basketball second level (15-19 years old) juvenile training. Combined means an harmonica and intelligent cohesion, interrelation between physical and technical workout, proposed, in particular periods of the year. Objectives. We are therefore in the categories under nineteen, and sometimes under seventeen years old. This kind of job doesn't remove that such a practice methodology is also used broadly by single athletes and not necessarily only in juvenile sectors that find necessary for some players a kind of additional diversified workout from usual the groupwork for varied motivations, that go from a possible delay on preparation or technical gaps to teach to be competitive in the proper group as well as towards the opponent. Method and Template. Here our following individual proposal has been, in real, performed by single athletes, on his spontaneous application around July, normally absolute or relative athletes rest period. This doesn't remove the following possibility for an athlete, very stimulated, in our case, we can say, autostimolated, to be able to effect a certain of type of diversified and specialized work-out of improvement. However what has to be maintained, in our opinion, is a period of absolute rest of about a pair of weeks, if not four weeks in case of younger athelets, one week more or less, in which the athlete must try to "reload the physical and psychological battery" for the beginning of the new sport season. Conclusions. Good feeling between sport operators and the individuals. Very high improvement both in technical-athetical way and in psychological one.